Knowledge management in an open innovation ecosystem: Building an age-friendly smart living environment - Weck. M.; Tamminen, P.; Ferreira, F. (ISPIM Connects Bangkok – Partnering for an Innovative Community, 2020)
An age-friendly smart living environment (SLE) is a common target of governments and businesses worldwide that enable seniors to continue living a comfortable, independent, and active life outside of any institutional care settings. A critical factor for building such SLEs is effective knowledge management (KM) that supports innovation actors to screen and accelerate the uptake of appropriate innovative products and services. The literature review revealed a need for an empirical study on KM in the context of open innovation ecosystems. The present study sought to identify key determinants of KM within the open innovation ecosystem through the integrated use of fuzzy cognitive mapping. A conceptual framework of KM fundamental factors and their cause-and-effect relationships was developed based on the insights obtained from the experts who participated in a focus group workshop and two panel meetings. The special focus was placed on the role of senior citizens in supporting KM.